Stratigraphic and Earth System approaches to defining the Anthropocene. Issue 8 (12th August 2016) - Steffen, Will; Leinfelder, Reinhold; Zalasiewicz, Jan; Waters, Colin N.; Williams, Mark; Summerhayes, Colin; Barnosky, Anthony D.; Cearreta, Alejandro; Crutzen, Paul; Edgeworth, Matt; Ellis, Erle C.; Fairchild, Ian J.; et al.
Abstract: Stratigraphy provides insights into the evolution and dynamics of the Earth System over its long history. With recent developments in Earth System science, changes in Earth System dynamics can now be observed directly and projected into the near future. An integration of the two approaches provides powerful insights into the nature and significance of contemporary changes to Earth. From both perspectives, the Earth has been pushed out of the Holocene Epoch by human activities, with the mid‐20th century a strong candidate for the start date of the Anthropocene, the proposed new epoch in Earth history. Here we explore two contrasting scenarios for the future of the Anthropocene, recognizing that the Earth System has already undergone a substantial transition away from the Holocene state. A rapid shift of societies toward the UN Sustainable Development Goals could stabilize the Earth System in a state with more intense interglacial conditions than in the late Quaternary climate regime and with little further biospheric change. In contrast, a continuation of the present Anthropocene trajectory of growing human pressures will likely lead to biotic impoverishment and a much warmer climate with a significant loss of polar ice. Key Points: Stratigraphy and Earth System science have built a multidisciplinary approach for understanding Earth evolution, including the advent of the Anthropocene. Both approaches provide strong evidence that human activities have pushed the Earth into the Anthropocene, starting from the mid‐20th century. Potential scenarios for the future Anthropocene range from more intense interglacial conditions to a greenhouse state with much less polar ice.